2022
DOI: 10.1364/prj.462050
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency InGaN red micro-LEDs for visible light communication

Abstract: In this study, we present a high-efficiency InGaN red micro-LED fabricated by the incorporation of superlattice structure, atomic layer deposition passivation, and a distributed Bragg reflector, exhibiting maximum external quantum efficiency of 5.02% with a low efficiency droop corresponding to an injection current density of 112    A / cm 2 . The fast carrier dynamics in the InGaN is characterized by using time-resolved p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 70 publications
1
23
2
Order By: Relevance
“…The central wavelength and FWHM of the EL mission as a function of current density for the InGaN red micro-LEDs with 1st and 2nd modified DBRs are shown in Figure 5 . As Figure 5 a shown, the peak position of the EL emission shows a blue shift of 16 nm which is much smaller than that in our previous work [ 36 ]. The FWHM of EL emission is broadened from 40 nm to 53 nm when the current density increased from 32 A/cm 2 to 400 A/cm 2 .…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…The central wavelength and FWHM of the EL mission as a function of current density for the InGaN red micro-LEDs with 1st and 2nd modified DBRs are shown in Figure 5 . As Figure 5 a shown, the peak position of the EL emission shows a blue shift of 16 nm which is much smaller than that in our previous work [ 36 ]. The FWHM of EL emission is broadened from 40 nm to 53 nm when the current density increased from 32 A/cm 2 to 400 A/cm 2 .…”
Section: Resultscontrasting
confidence: 57%
“…Even though there were several studies of InGaN red micro-LEDs, the EQE and the blue shift phenomenon of the device still have much room for improvement. In our previous work published in 2022 [ 36 ], a 25 µm-sized micro-LED was grown on a c-plane patterned sapphire substrate (PSS) by metal-organic vapor-phase epitaxy (MOVPE). The mainly epitaxial structures include an undoped-GaN layer to reduce the residual stress, 15 pairs of GaN/In 0.08 Ga 0.92 N superlattices (SL) layers, an InGaN blue single-quantum well (SQW), an InGaN red double-quantum well (DQWs) with a high indium content, a barrier layer, and contact layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although semipolar and m-plane micro-LEDs have excellent performance, the cost and difficulty of mass production make them challenging. As a result, in recent years, researchers have been studying ways to improve the performance of c-plane micro-LEDs, such as using strain-released layer [ 41 ], superlattice [ 56 ], and staggered quantum well [ 49 ].…”
Section: Challengesmentioning
confidence: 99%
“…Although the QCSE of the LEDs can be decreased by growing them on semipolar substrates, InGaN red micro-LEDs grown on c-plane substrates are currently the best option due to their compliance with existing manufacturing techniques. Recently in 2022, Huang et al demonstrated red-emitting InGaN-based micro-LED with high efficiency and high modulation bandwidth by incorporating superlattice structure and distributed Bragg reflector [ 56 ]. The epitaxial structure of the LED comprised blue InGaN single-QW (SQW) and red InGaN double-QWs (DQWs) as the active region.…”
Section: Progress For Micro-led Vlc In Yellow–green To Red Emission W...mentioning
confidence: 99%